Depression Levels Of Prisons In Class II A Correctional Institutions Bulukumba Regency - Safruddin; Nurlina; Anel Ariansyah (Comprehensive Health Care, 2020)
A depressive disorder is a serious mental problem characterized by feelings of anxiety and sadness. Depressive disorders have increased from year to year, where the total number of people living with depression in the world is 322 million, this is supported by WHO 2017 data. Generally, someone in a depressed state experiences feelings of sadness, anxiety, or emptiness, and the impact that is caused if depression is not treated immediately, it will have an impact on oneself such as low self-esteem, social isolation, and even suicide attempts. Besides that, it will also have an impact on the people around it. The purpose of this study is to know the description of the level of depression in prisoners in Class II A Penitentiary in Bulukumba Regency in 2020. The research design used in this study is a descriptive research design with a cross-sectional approach. The affordable population in this study were inmates with all cases totaling 194 people with a sample size of 85 respondents. The sampling technique using a systematic random sampling method selects a sample from the population systematically. Data were collected using a questionnaire sheet. Based on the results of the research conducted, it was shown that the frequency distribution of the level of depression of the 85 prisoner respondents experienced mild depression as many as 64 respondents (75.3%) then moderate depression was 14 respondents (16.5%) and 7 respondents (8.2%) were not depressed. In all cases, the depression level of prisoners in class II A prisons in Bulukumba district experienced mild depression. Researchers suggest that further the sample size can be added so that data collection is more accurate and can be linked to other variables that can cause depression